Olive Fruit Blends Modulate Lipid-Sensing Nuclear Receptor PPARγ, Cell Survival, and Oxidative Stress Response in Human Osteoblast Cells. (3rd October 2018) - Ammendola, Sergio; Cocchiola, Rossana; Lopreiato, Mariangela; Politi, Laura; Scandurra, Roberto; Giusti, Anna Maria; Scotto d'Abusco, Anna
ABSTRACT: Objective : The aim of the present study was to investigate how different extravirgin olive oils (EVOOs), obtained by blending Olea europea cultivars, could influence the cell growth, the response to inflammatory stimuli, and oxidative stress in a culture of the osteosarcoma cell line Saos-2. Methods : Three different extravirgin olive oils were physicochemically characterized, determining the free acidity, the oxidation status, the polyphenols content, and the antioxidative activity. Moreover, the effects on Saos-2 cell culture were determined, studying the mRNA expression level by real-time polymerase chain reaction (PCR) assays and the antioxidative activity using fluorescent probes. Results : The cultivars used in the south of Italy, yield extravirgin oils with different amount of fatty acids and polyphenols, which counteract induction of proinflammatory cytokines and regulate free radical production in hydrogen peroxide-stimulated cells. In vitro analysis using the human osteoblast cell line Saos-2 showed that the addition of oils to cell culture simulated a hypoxic stress followed by a reoxygenation period, during which the antioxidant activity of extravirgin olive oils protected cells from oxidative damages. On the other hand, the mRNA expression levels of factors involved in inflammatory processes, cell growth recovery, and antioxidant response, as heme oxygenase-1, were differently stimulated by EVOOs. Moreover, peroxisome proliferator activated receptor γ (PPARγ) was differently modulated by EVOOs. Conclusion : These findings show that the blending of different extravirgin olive oil can impact an osteoblast cell line, in particular regarding cell growth recovery and oxidative stress.